Extreme sensitivity to ultraviolet light in the fungal pathogen causing white-nose syndrome of bats - Jonathan M. Palmer (Nature Portfolio, 2018)
White-nose syndrome, caused by the fungus Pseudogymnoascus destructans, is decimating North American bats. Here, Palmer et al. use comparative genomics to examine the evolutionary history of this pathogen, and show that it has lost a crucial DNA repair enzyme and is extremely sensitive to UV light.